Melatonin - The Hormone of Darkness and Its Therapeutic Potential and Perspectives 2020
DOI: 10.5772/intechopen.90935
|View full text |Cite
|
Sign up to set email alerts
|

Review of Melatonin in Horticultural Crops

Abstract: Melatonin is an indoleamine, abundant in animals and plants, which has the functions of regulating circadian rhythm, improving immunity and anti-aging in animals, and is a good health care product beneficial to human health. Recent studies have shown that melatonin has physiological functions including regulating plant growth, promoting seed germination, controlling root development and delaying leaf senescence. The antioxidant properties of melatonin give it the ability to strengthen plants' resistance to str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…The results of oxidative stress scavengers’ activity showed that melatonin improved certain parameters at a higher rate with one bacterial inoculant over the other, indicating preferential induction/synergism of some microbes with melatonin. Melatonin has been reported to regulate rhizogenesis and fortify reactive oxygen species (ROS) scavenging mechanisms, root architecture, photosynthetic capacity, and ionic balance of plants under salinity stress ( Yan et al., 2020 ; Altaf et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of oxidative stress scavengers’ activity showed that melatonin improved certain parameters at a higher rate with one bacterial inoculant over the other, indicating preferential induction/synergism of some microbes with melatonin. Melatonin has been reported to regulate rhizogenesis and fortify reactive oxygen species (ROS) scavenging mechanisms, root architecture, photosynthetic capacity, and ionic balance of plants under salinity stress ( Yan et al., 2020 ; Altaf et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few reports on the improvement in plant performance after the combined application of microbes and melatonin (Liu et al, 2021b), which support our results that show synergistic effects with bacterial inoculants and melatonin. Yan et al (2020) reported that pre-treatment with melatonin reduced membrane damage and oxidative stress in rice under salinity. Thus, the stage of application, as well as the concentration are crucial for the melatonin role.…”
Section: Discussionmentioning
confidence: 99%
“…The root system also has the capability to inhibit the uptake and translocation of toxic ions to other tree parts [ 69 ]. Identification of tolerant/sensitive germplasm is clearly based on the root architecture of fruit trees and the ability of the root system to inhibit toxic ions from the soil [ 70 ].…”
Section: Response and Adaptation Mechanism Under Salinity Stressmentioning
confidence: 99%
“…Exogenous application of MT decrease salt inhibition for plants growth as well as increase biomass accumulation (Jiang et al, 2016). In addition, MT application increased growth attributes, accumulation of biomass and improved assimilation of carbon in plant tissues due to increase the photosynthetic rate and pigments content under stress conditions (Hernández-Ruiz et al, 2005 andYan et al, 2020).…”
Section: Effect Of Anti-stressors Treatmentsmentioning
confidence: 99%